Nutrition for sport, exercise, and health - Spano, Marie A. MS, RD, CSCS, CSSD; Kruskall, Laura J. PhD, RDN, CSSD, LD, FACSM, FAND; Thomas, D. Travis PhD, RDN, CSSD, LD, FAND (Champaign, IL Human Kinetics, 2024)
Nutrition for sport, exercise , and health, second edition, blends applied content with updated research-based guidelines to help students distinguish between nutrition recommendations backed by science and the plethora of misinformation available in the field. Students first discover the role nutrition plays in overall well-being. Next, they learn the role that support health and active lifestyle. Then, the function of micronutrients in health and performance is covered. Finally, the text concludes with the application of nutrition principles, with guideance on how to properly fuel for sport, exercise, and health
Chapter 1. Optimizing health and well-being throughout the lifespan -- Chapter 2. Energy metabolism -- Chapter 3. Carbohydrate -- Chapter 4. Fat -- Chapter 5. Protein -- Chapter 6. Vitamins -- Chapter 7. Minerals -- Chapter 8. Water and electrolytes -- Chapter 9. Nutritional supplements and other substances commonly used in sport -- Chapter 10. Body weight and composition -- Chapter 11. Nutrition for aerobic endurance -- Chapter 12. Nutrition for resistance training -- Chapter 13. Changing weight and body composition -- Chapter 14. Nutrition concerns for special populations
Includes bibliographical references and index
Keywords: Physical fitness -- Nutritional aspects; Athletes -- Nutrition; Exercise -- Physiological aspects